Annotations on Galatians and Ephesians - Erasmus, Desiderius (Collected works of Erasmus, 2017)
Volume 58 in the Collected Works of Erasmus series contains, for the first time, the English translation of Erasmus' Annotations on Paul's Epistles to the Galatians and Ephesians.